Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet C7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Geological observations in Gjelsvikfjella, Mühlig-Hogmanfjella and western Orvinfjella during NARE 96/97 - Austrheim, Håkon; Elvevold, Synnøve; Engvik, Ane K; Paulsson, Oskar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geologi

Geodetic measurements in Dronning Maud Land - Barstad, Bjørn; Eiken, Trond; Finnes, Randi; Øvstedal, Ola (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geodesi; målinger

Geodetic and topographic work - Barstad, Bjørn; Eiken, Trond; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; geodesi; topografi

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Distribution and food consumption of crabeater seals off Dronning Maud Land - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; seler; zoologi

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Full-text: https://sora.unm.edu/sites/default/files/journals/auk/v114n03/p0333-p0340.pdf
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi